THE INFLUENCE OF FINELY GROUND MINERAL ADMIXTURE (FGMA) ON EFFLORESCENCE - Ming Wei, Ong; Norsuzailina, Mohamed Sutan (UNIMAS, 2022)
Efflorescence phenomenon on concrete is not new and found in the form of white deposits on surfaces of concrete. Incorporation of Finely Ground Mineral Admixture (FGMA) in concrete to prevent occurrence of efflorescence is based on reduction of portlandite, densified microstructure and thus enhanced watertightness. The magnitude of efflorescence in term of percentage of calcium carbonate formation of FGMA modified mortar were evaluated at water-cement ratio of 0.3, 0.4 and 0.5 with 10%, 20%, and 30% of cement replacement by weight. The samples were tested with chemical analysis at 7, 14, 21, 28, 60 and 90 days. The FGMA additions into mortar were comparing with ordinary mortar to evaluate enhanced performance of FGMA modified mortar toward efflorescence. The results of this experiment showed that addition of FGMA into mortar caused less formation of calcium carbonate as partial replacement of cement with certain w/c ratio and percentage of cement replacement.